Introducing Modern Italy's new editors. Issue 1 (February 2015) - Unknown
Abstract : As the new editors of Modern Italy for the period 2015–2019, we are very conscious of the high bar set by our predecessors, Philip Cooke and John Foot. Together they guided the transition to ScholarOne's manuscript flow system, increased the journal's already dynamic range of publication, and further enhanced its international reputation among scholars of Italy as well as the academic publishing industry. They achieved all this during what their 2010 editorial rightly described as a 'critical time for Italian studies in the UK'. We thank them and their editorial team warmly for handing over to us, and to ASMI, a journal in excellent form, despite the very real challenges of the times.